Labor Productivity Disparities in the Planning and Implementation Phases - Aditya Rachmad Prasetyo; I Nyoman Dita Pahang Putra; Suliman Badawi Ahmed (Department of Civil Engineering, Politeknik Negeri Bandung, 2025)
Infrastructure plays an important role in promoting connectivity, economic growth, and community welfare. In the construction sector, labor productivity is a crucial factor that determines project accomplishment. This study aims to analyze and compare the labor productivity during planning and implementation phase using secondary data as the main source. Data sources include a valid project documents and related regulation. The analysis carried out to find the planned labor productivity based on the cost budget plan and time schedule, the realized productivity value based on the cost budget plan and daily report, and the comparison between the two. The results showed that there was a significant variation in the labor productivity level between the planning and implementation phases of the project. There was an increase in labor productivity in several types of work including plastic cast installation 47%, D36-300 dowel installation 12%, 2-layer wiremesh 35%, Rigid Pavement K-350 28%, and joint filler work 71%. On the other hand, works such as flooring and tie-bar works experienced a decrease in labor productivity by 47% and 11%. These findings provide valuable insights for project management to improve future planning and execution, emphasizing the need for continuous labor productivity evaluation to achieve optimal result.